2022
DOI: 10.1021/acs.est.1c07011
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Photochemical Air Pollution in California’s San Joaquin Valley to Spatially and Temporally Resolved Changes in Precursor Emissions

Abstract: Ground-level ozone adversely affects human health and ecosystems. The effectiveness of control programs depends on which precursor(s) are controlled, by how much, and where and when emission reductions occur. We use the adjoint of the Community Multiscale Air Quality model to investigate odd oxygen (O x ≡ O3 + NO2) sensitivities in California’s San Joaquin Valley (SJV) to precursor emissions from local and upwind sources. Sensitivities are mapped and disaggregated by hour and day. Taken together, impacts of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Previous studies have identified two upwind air basins, the SV and the SF Bay, as important contributors to O x concentrations in the SJV. These upwind contributions arise mostly from prior-day rather than same-day precursor emissions , and include combined effects from transport of precursors emitted and ozone formed in the upwind areas.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have identified two upwind air basins, the SV and the SF Bay, as important contributors to O x concentrations in the SJV. These upwind contributions arise mostly from prior-day rather than same-day precursor emissions , and include combined effects from transport of precursors emitted and ozone formed in the upwind areas.…”
Section: Resultsmentioning
confidence: 99%
“…All simulations are conducted for a standard set of meteorological conditions, representing a weeklong period (27 July to 2 August 2000) that is selected based on results of a cluster analysis . This time period has been the focus of multiple modeling and measurement studies , and is representative of a recurring ozone-inducing meteorological regime . Its flow patterns are close to the summer average (Figure S1) with prevailing high temperatures (Figure S2).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations